The Political Life in The Era of the Babylonian King Nabonidus (Web of Technology: Multidimensional Research Journal, 2023)
The Chaldean tribes inherited the rule of Babylon during the first millennium BC and the period of rule of these Chaldean tribes is known as the Neolithic period. Despite the existence of many studies, these studies were in the period of the eighties, nineties and the beginning of the 2000s, if there is little information about the Neo-Babylonian period and the kings of Babylon, as well as King Nabonid (Nabonid), this research has adopted modernity after the development of modern readings, studies and translations about this king, as it has kept pace with developments and kept pace with and contemporary with this development, as well as encouraging and his view that previous studies need to be reviewed and a new study due to the availability of modern sources and the availability of more information than previous studies that lack much information, so we addressed the special political conditions of King Nabonid, especially the settlement in Taima and the administration of Babylon from there, as well as shedding light on the reasons for this settlement and the reasons for leaving Babylon.